The political economy of agricultural policy reform in India: Fertilizers and electricity for irrigation - Birner, Regina; Gupta, Surupa; Sharma, Neeru (International Food Policy Research Institute, 2011)
Agricultural policy reform is one of the major challenges facing India today. Such reform is required in order to reduce poverty through faster agricultural growth and to promote more sustainable use of natural resources while ensuring food security. Subsidy policies that promote the use of fertilizer and of electricity for groundwater irrigation are in particular need of reform. While subsidies for these two inputs played a crucial role in achieving India's Green Revolution, they have been criticized during the past decade for benefiting large-scale farmers more than smallholders, placing a fiscal burden on the state, and having negative environmental effects. By analyzing the evolution of these input subsidy policies and examining the political processes involved in efforts to reform them, this study throws new light on the factors that have so far prevented a move toward more pro-poor and environmentally sustainable agricultural input policies in India. The authors show that electoral politics, institutional factors, and policy paradigms or belief systems all play an important role in blocking reform. They identify several policy reform options, as well as political strategies that can overcome past obstacles to reform. Community-based policy solutions, new coalitions for policy reform, fresh approaches to the policy debate, innovative and consensus-oriented forms of deliberation, and effective use of research-based knowledge can all make positive contributions to Indian policy reform. The analyses and proposals presented in this study will be a valuable resource for policymakers and stakeholders concerned with the politics of agricultural development.